2014
DOI: 10.3329/bjar.v38i4.19032
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of fungicides and organic oils to control powdery mildew disease of jujube (Ziziphus mauritiana Lam.)

Abstract: Powdery mildew (Oidium erysiphoides f.sp. ziziphi) is the major disease of Indian jujube (Ziziphus mauritiana) in Bangladesh. An experiment was conducted to test the efficacy of six fungicides, two organic oils, and a detergent against the disease. Tested fungicides were Tilt (Propiconazole) @ 0.05%, Folicur (Hexaconazole) @ 0.1%, Bavistin DF (Carbandazim) @ 0.2%, Dithane M-45 (Mancozeb) @ 0.3%, Thiovit 80 WG (Sulpher) @ 0.3%, and Cupravit (Copper) @ 0.3%, the oils were Mustard oil @ 0.5% and Neem oil 0.5%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Kumar and Chandel (2018) obtained the highest efficacy with Bacillus subtilis, neem oil and Allium sativus at their higher concentrations under in vitro studies of powdery mildew of rose. Hoque et al (2013) observed that mustard oil (0.5%) and neem oil (0.5%) significantly decreased the severity of the powdery mildew disease of jujube. Mishra et al (2017) reported the efficacy of neem leaves extract, neem oil, eucalyptus leaves extract, Trichoderma harzianum, Pseudomonas fluroscens and hexaconazole against powdery mildew disease of garden pea where minimum per cent disease incidence (31.80%) and maximum pod yield (12.6 q/ha) was found with neem oil.…”
Section: Resultsmentioning
confidence: 89%
“…Kumar and Chandel (2018) obtained the highest efficacy with Bacillus subtilis, neem oil and Allium sativus at their higher concentrations under in vitro studies of powdery mildew of rose. Hoque et al (2013) observed that mustard oil (0.5%) and neem oil (0.5%) significantly decreased the severity of the powdery mildew disease of jujube. Mishra et al (2017) reported the efficacy of neem leaves extract, neem oil, eucalyptus leaves extract, Trichoderma harzianum, Pseudomonas fluroscens and hexaconazole against powdery mildew disease of garden pea where minimum per cent disease incidence (31.80%) and maximum pod yield (12.6 q/ha) was found with neem oil.…”
Section: Resultsmentioning
confidence: 89%
“…Pseudoidium ziziphi is a major disease of Z. mauritiana in India, Pakistan and Bangladesh (Sharma & Panwar, ; Braun & Cook, ; Hoque et al ., ). It is an obligate airborne pathogen with the mycelia and conidiophores remaining external on the host (Azam‐Ali et al ., ).…”
Section: Natural Enemies In the Native Rangementioning
confidence: 97%